Pengaruh Konsentrasi Sari Jahe Merah (Zingiber officinale Var. Rubrum) Terhadap Hasil Uji Sensoris Permen Kelapa Jahe - Ronny Robot; Maya Ludong; Christine Mamuaya (COCOS, 2019)
Abstract This study aims to determine the amount of red ginger juice concentration on the manufacture of coconut candy based on sensory tests. This study used a Completely Randomized Design (CRD) 4 treatment with 3 replications namely, A (4% red ginger juice), B (8% red ginger juice), C (12% red ginger juice), D (16% red ginger juice). Then a quantitative test for water content, ash content, and reducing sugar content is carried out, this is done for the most preferred sample. Based on organoleptic testing, the level of preference for taste, color, aroma, and texture of ginger coconut candy is accepted by panelists with neutral to like criteria. The most preferred ginger coconut candy is one made with a 4% red ginger juice concentration. Then a further test is done, namely 4.90% water content, 2.06% ash content and 7.24% reducing sugar content. Keywords: Coconut Candy, Red Ginger Juice, Palm Sugar